Analisis Pembangunan Infrastruktur dalam Pemenuhan Aksesibilitas Pelayanan Dasar di Kota Serang - Tiwi Rizkiyani; Sierfi Rahayu (Jurnal Ilmu Administrasi Negara, 2025)
Infrastructure is an important aspect in supporting the accessibility of public services, especially basic services. Basic services are public services provided by the government to meet the basic needs of the community covering various aspects, including health, education, public housing and residential areas, as well as public works and spatial planning. The ease of accessibility of basic services is supported by the availability and quality of adequate infrastructure. Improving regional infrastructure is one of the development priorities in Serang City. There are still several problems related to infrastructure development that have an impact on the fulfillment of public service accessibility in Serang City, including the problem of road damage that has an impact on flooding, lack of street lighting, not optimal fulfillment of clean water, lack of maintenance of public facilities, uneven and fulfilled green open space (RTH), and still low community participation in infrastructure development. This study aims to analyze infrastructure development in fulfilling the accessibility of public services in Serang City by using the theory of Gibson et al (1997) which consists of four dimensions in assessing the success of infrastructure development, namely physical availability, physical quality, suitability, and utilization. Using qualitative methods, the results show that infrastructure development in Serang City is good and supports the accessibility of basic services. This is because it is supported by the policies of the Local Government of Serang City and the commitment of all authorized Regional Apparatus Organizations (OPD). However, the availability of infrastructure needs to be improved evenly in each sub-district in Serang City and its maintenance needs to be carried out on an ongoing basis so that the benefits can be optimally felt by the people of Serang City. Keywords: Accessibility, Infrastructure, Basic Public Services, Development.